Use of a Modified Comprehensive Pain Evaluation Questionnaire: Characteristics and Functional Status of Patients on Entry to a Tertiary Care Pain Clinic - Jennifer M Nelli; Keith Nicholson; S Fatima Lakha; Ada F Louffat; Luis Chapparo; Julio Furlan; Angela Mailis-Gagnon (Pain Research and Management)
BACKGROUND: With increasing knowledge of chronic pain, clinicians have attempted to assess chronic pain patients with lengthy assessment tools.